1826-1828 թթ. ռուս-պարսկական պատերազմի հայկական աղբյուրները - Հովհաննիսյան, Հայկազ (Մատենադարան)
In addition to Russian sources, Armenian documents are also important in the study of the Russian-Persian war of 1826-1828. Such documents are kept in the Lazarev archive at Matenadaran. These are letters of famous Armenian political and religious figures, which not only supplement the history of the Russian-Persian war but also provide important details about the events that took place in the eastern part of Armenia at the beginning of the 19th century. В изучении русско-персидской войны 1826-1828 гг., помимо русских источников, важное место занимают армянские документы. Таковые хранятся в архиве Лазаревых, в Матенадаране. Это письма и рассуждения известных армянских политических и духовных деятелей, которые не только дополняют историю русско-персидской войны, но также сообщают важные подробности событий, происшедших в начале XIX в. в Восточной Армении.
Keywords: Պատմություն